Peran Supervisi Akademik dalam Meningkatkan Kualitas Pemebelajaran: Studi Literatur tentang Strategi dan Implementasi - Julia Salsabila; Adillah Naryawati; Ermita; Fifin Wildanah (CV. ITTC INDONESIA, 2025)
The effectiveness of education in schools heavily relies on the caliber of learning. Nonetheless, several issues persist, including insufficient teacher skills, a lack of creativity in teaching practices, and ineffective learning oversight, which constitute significant barriers. This article intends to investigate how academic supervision contributes to enhancing learning quality by utilizing a literature review methodology. The approach entails examining a variety of academic resources, including scholarly articles, literature, and pertinent organizational documents. Findings suggest that when academic supervision is thoughtfully structured and implemented through careful stages of planning, execution, assessment, and follow-up, it can elevate teacher professionalism and the effectiveness of educational activities. Implementing strategies the right way at each phase will reinforce the position of teachers as engaged and reflective guides. In summary, academic supervision functions not only as a tool for assessment but also as a developmental journey that fosters ongoing advancement in learning quality.